Marine Bacteria from Eastern Indonesia Waters and Their Potential Use in Biotechnology - Yosmina H Tapilatu (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
Indonesian vast marine waters, which constitute 81% of the country’s total area, have a great potential in terms of marine bacteria biodiversity. However, marine bacteria are still under-explored in Indonesia, especially in its eastern area. Known as one of the biodiversity hotspots worldwide, this area surely harbors various marine bacteria of particular interest. Despite the growing number of oceanic expeditions carried out in this area, only little attention has been attributed to marine bacteria. Limited literatures exist on the isolation of marine bacteria producing compounds with potential biotechnological applications from the aforementioned waters. There are two main causes of this problem, namely lack of infrastructures and limited competent human resources. In this paper, I will highlight the preliminary results of isolation and bioprospecting attempts on this group of bacteria during the last fifteen years. These results indicate that research activities on marine bacteria in this area need to be intensified, to uncover their potential applications in various biotechnological fields.Keywords: marine bacteria, eastern Indonesian waters, biotechnological application